The visual culture of Catholic Enlightenment - Johns, Christopher M. S. (Pennsylvania State University Press, 2015)
Introduction : Rome and the Catholic Enlightenment in historical context -- Ecclesiastical reform and the European public : Italian Jansenism and the Catholic Enlightenment -- Sanctity and social utility : making saints in the era of Catholic Enlightenment -- The papacy and the patrimony I : Corsini cultural initiatives on the Capitoline Hill -- The papacy and the patrimony II : the expansion of the Capitoline museums under Benedict XIV and Clement XIII -- Enlightened administration and polite conversation : Clement XII and Benedict XIV on the Quirinal Hill -- Roman spaces of Catholic Enlightenment : sacred sites and institutions of social utility -- Popes, episcopacy, and the "good bishop" of Catholic Enlightenment -- Epilogue : two Portuguese earthquakes and the end of Catholic Enlightenment